2015
DOI: 10.1088/0964-1726/24/4/047001
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of a novel magnetorheological brake with coils placed on the side housings

Abstract: In the design of a traditional magnetorheological brake (MRB), coils are often placed on the cylindrical housing of the brake. This results in many disadvantages such as a ‘bottle-neck’ problem of magnetic flux. Moreover, in this design a nonmagnetic bobbin is required, and difficulties in manufacturing and maintenance exist. In order to resolve this problem, in this study a new configuration of MRB with coils placed on the side housings of the brake is proposed, optimally designed and experimentally evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(65 citation statements)
references
References 16 publications
(20 reference statements)
0
62
0
Order By: Relevance
“…In this design method, the torque level is similar to the conventional one, but the manufacturing cost is reduced substantially. In 2015, a new model of the MRF brake was proposed based on the changeable structure of the electric or/and magnetic coil (Nguyen et al, 2015). This was made possible by placing the electric coil at the outside of the housing.…”
Section: Mrf Brake and Mrf Clutchmentioning
confidence: 99%
“…In this design method, the torque level is similar to the conventional one, but the manufacturing cost is reduced substantially. In 2015, a new model of the MRF brake was proposed based on the changeable structure of the electric or/and magnetic coil (Nguyen et al, 2015). This was made possible by placing the electric coil at the outside of the housing.…”
Section: Mrf Brake and Mrf Clutchmentioning
confidence: 99%
“…In the above, R i is the radius of the point i in the disc profile as shown in Figure 4, l is the length of the inclined gap, φ is the inclined angle, h is the height of the tooth, µ Ei and τ Ei are the post-yield viscosity of the MRF in the gap E i , µ Ii and τ Ii are the post-yield viscosity of the MRF in the gap I i , and µ c and τ c are the post-yield viscosity of the MRF in the gap denoted by C. In this study, the induced yield stress and post-yield viscosity of MRF are functions of the applied magnetic density across the MRF duct, which are approximated by [36]:…”
Section: The Rotary Mr Brakesmentioning
confidence: 99%
“…B is the applied magnetic density. In this study, the commercial MRF made by Lord Corporation (Cary, North Carolina, United States), MRF132-DG, was used and its rheological properties according to Equation (5) are as follows [36]:…”
Section: The Rotary Mr Brakesmentioning
confidence: 99%
“…Later, Nguyen et al (2014a) evaluated the effect of different shapes of envelope such as the rectangular, the polygonal and the spline to the performance and the mass of MRBs. Recently, Nguyen et al (2014bNguyen et al ( , 2015 proposed a new configuration of MRB in which a magnetic coil is wound on each side of the housing of the MRB (in this research, it is named as side-coil MRB). The results showed that, with this configuration, some disadvantages of the traditional MRBs such as the "bottle-neck" problem of magnetic flux, the non-magnetic bobbin requirement, difficulties in manufacturing and maintenance can be eliminated or minimized.…”
Section: Introductionmentioning
confidence: 99%